Rancang Bangun Double Ring Infiltrometer Untuk Pengukuran Penambahan Ketinggian Campuran Sabut Kelapa Dan Pasir - Moch Rido Maulana; Mukhlis Ali (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2023)
In Indonesia, currently the problem of water infiltration into the ground has become a major problem in various areas, especially urban areas. One of these problems is influenced by changes in land use due to growth and increased population activity. In general, in Indonesia the transfer of land use from green open spaces to buildings. As a result of the lack of a good water absorption rate can cause many flood disasters. To prevent flooding, knowledge about the rate of water infiltration in an area is important. To measure the infiltration rate, infiltrometer technology is needed. The design of the double ring infiltrometer has 3 stages, namely first using 304 stainless steel material, the next stage is the rolling process using a 6 × 1300 mm BB613RL rolling machine, and the last stage is the welding process using TIG welding. The effect of adding a mixture of coconut coir and sand on changes in the infiltration rate that occurs in both rings, in this change the slowing of the infiltration rate does occur because the mixture of coconut coir and sand blocks water infiltration directly into the soil. Thus it can be concluded that the addition of a mixture of coconut coir and sand as a ground cover does not have much impact on the rate of water absorption into the soil, especially in the direction of water absorption perpendicular to the soil.